Expression and clinicopathological correlations of retinoid acid receptor responder protein 1 in renal cell carcinomas. (July 2016) - Zimpfer, Annette; Dammert, Friedericke; Glass, Aenne; Zettl, Heike; Kilic, Ergin; Maruschke, Matthias; Hakenberg, Oliver W; Erbersdobler, Andreas
Aim: To evaluate the expression and prognostic value of RARRES1 at protein level in renal cell carcinoma (RCC).Materials & methods: Expression profile of RARRES1 was analyzed in 903 documented RCC followed by clinicopathological correlations and survival analysis.Results: RARRES1 expression was seen in 72.5% of RCC. A stronger RARRES1 expression was seen in high grade compared with low grade RCC (p < 0.001). Logrank tests revealed shorter overall survival in RARRES1 positive RCC (p = 0.006) and in pT1/2 tumors with RARRES1 expression (p = 0.002).Conclusion: The variable expression profile in low and high grade RCC may reflect and confirm the differences of previous gene expression analysis. There was a significant prognostic value of RARRES1 expression in patients with RCC, especially in pT1/2 tumors.